Pancasila as a Legal Political Paradigm: Implications for the Judicial System and Law Enforcement in Indonesia - Albert Limbong Sintong; Tasya Darosyifa (International Forum of Researchers and Lecturers, 2024)
Pancasila as a grundnorm plays an important role in the legal political paradigm in Indonesia as the basis for the formation of the legal system. All laws in Indonesia must be based on Pancasila as the source of all legal sources. The main issue studied is the extent to which Pancasila influences the legislative process and legal policies to realize a fair judicial system, as well as how its values can reform the judicial system and improve the quality of law enforcement. This study uses a normative method with a conceptual approach supported by the analysis of the hierarchy theory of legal norms and development law. The results of the study show that although Pancasila has been recognized as a grundnorm in the legal hierarchy, its implementation in legislation and legal policies still often faces obstacles, so a more responsive and inclusive legal system reform based on Pancasila values is needed.